Determinasi Self Efficacy, Kompetensi, Fasilitas Kerja Terhadap Kinerja Kader PPKBD Kelurahan di Kota Batam yang Melalui Motivasi Kerja - Jorgis Butarbutar; Bambang Satriawan (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purpose of this study was to determine whether Self Efficacy, Competence, work facilities and work motivation had a direct effect on performance and to find out whether Self Efficacy, Competence, Work facilities had a direct effect on work motivation and to examine the indirect influence carried out in urban villages in the city. Batam. The sample of this research is PPKBD Cadres who work in Kelurahan. Questionnaires distributed as many as 172 respondents and all returned. To analyze the data of this study using multiple regression analysis technique using SmartPLS software. Self efficacy and work facilities have no significant direct effect on cadre performance. Competence and work motivation on performance have a significant direct effect. Self efficacy, competence and work facilities on work motivation have a direct effect. The results of the indirect effect of self-efficacy, competence, work facilities on performance through work motivation have a significant effec